The Influence of Product Quality, Price Perception, and Brand Image on The Purchase Decision of Bimoli Cooking Oil at Alfamart Minimarket in Pasar Minggu Area, South Jakarta - Siti Maemunah; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the effect of product quality, price perception, and brand image on purchasing decisions for bimoli cooking oil at Alfamart minimarkets in the Pasar Minggu area of South Jakarta. This study uses primary data which is obtained from distributing questionnaires to 100 respondents using Bimoli cooking oil at the Alfamart minimarket in the Pasar Minggu area of South Jakarta and processing the data using the multiple linear regression analysis method on the SPSS 23 application. The results in this study that product quality, price perception, and brand image have a positive and significant effect on purchasing decisions for Bimoli cooking oil at Alfamart minimarkets in the Pasar Minggu area of South Jakarta. In this case, the positive and significant influence explains that the better product quality, price perception, and brand image will improve purchasing decisions for consumers.